IL-7 in SARS-CoV-2 Infection and as a Potential Vaccine Adjuvant - Bekele, Yonas; Sui, Yongjun; Berzofsky, Jay A. (Frontiers in Immunology, 2021)
IL-7/IL-7R signaling is critical for development, maturation, maintenance and survival of many lymphocytes in the thymus and periphery. IL-7 has been used as immunotherapy in pre-clinical and clinical studies to treat cancer, HIV infection and sepsis. Here, we discuss the critical function of IL-7 in diagnosis, prognosis and treatment of COVID-19 patients. We also summarize a promising role of IL-7 as a vaccine adjuvant. It could potentially enhance the immune responses to vaccines especially against SARS-CoV-2 or other new vaccines.